2022
DOI: 10.3389/fmicb.2022.1009310
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologically influenced corrosion of FeCoNiCrMn high-entropy alloys by Pseudomonas aeruginosa biofilm

Abstract: Pseudomonas aeruginosa is widely found in industrial water and seawater. Microbiologically influenced corrosion (MIC) caused by P. aeruginosa is a serious threat and damage to the safe service of steel materials. In this study, the MIC behavior of FeCoNiCrMn high-entropy alloy (HEA) by P. aeruginosa biofilm was investigated in the simulated marine medium. The maximum pitting depth of the HEA coupons in the P. aeruginosa-inoculated medium was ~4.77 μm, which was 1.5 times that in the sterile medium. EIS and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…MIC refers to the material degradation caused by microbial activities or corrosive microbial metabolites, which accounts for 20% of global corrosion costs [7][8][9]. Numerous studies have shown that some microorganisms can accelerate the corrosion of metals [10][11][12][13][14][15][16][17]. However, the effect of microorganisms on the corrosion resistance of organic coatings is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…MIC refers to the material degradation caused by microbial activities or corrosive microbial metabolites, which accounts for 20% of global corrosion costs [7][8][9]. Numerous studies have shown that some microorganisms can accelerate the corrosion of metals [10][11][12][13][14][15][16][17]. However, the effect of microorganisms on the corrosion resistance of organic coatings is rarely reported.…”
Section: Introductionmentioning
confidence: 99%